PENGARUH PEMBELAJARAN LITERASI TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS III SD NEGERI BIBISLUHUR 1 SURAKARTA TAHUN PEMBELAJARAN 2024/2025 - Fadhila Eka Hayyu; Hera Heru Sri Suryanti; Sarafuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of literacy based instruction on the reading comprehension skills of third-grade students at SD Negeri Bibisluhur 1 Surakarta. The research employed a quantitative approach with an experimental method using a one- group pretest-posttest design. The population consisted of all 28 students in class III A. Data collection techniques included tests, observation, and documentation. The research instruments were validated through validity and reliability tests, while data analysis was conducted using prerequisite tests and hypothesis testing with the Independent Sample t- test. The results of the study revealed that literacy-based instruction had a significant effect on improving students' reading comprehension skills. This was evidenced by an increase in the average student score from 48.21 in the pretest to 76.07 in the posttest. Most students shifted from the "not yet proficient" category to the "proficient" and even "highly proficient" categories